DEVELOPMENT OF STRUCTURAL SCHEME OF DOUBLE RING MEASURING ANTENNA - Ільницький, Л. Я.; Щербина, О. А.; Кленецька, К. В. (Science-based technologies, 2014)
In this paper the principle of double ring antenna system is considered. The following antenna system is capable of simultaneous measurement of the direction of wave arrival, as well as the module and orientation of the field intensity (polarization properties). Moreover, the problem of research is aimed to build an antenna system that could measure simultaneously the direction of wave arrival, module and orientation of the electric field in terms of relative software simplicity. For this purpose, it is advisable to use the ring emitters which divide the incident electromagnetic wave into a circular polarization orthogonal basis. For accurate determination of the polarization parameters antenna has two operating modes: direction finding and measurement. Direction finding mode requires binding to the chosen area coordinate system. Measurement mode is used after the direction finding mode and this mode should provide mechanical rotation of the plane of ring antennas. меC 2 W6 ежим измерения используется после режима пеленгации и для этого режима необходимо иметь возможность механического поворота плоскостей кольцевых антенн.